Complement receptor 3 mediates Aspergillus fumigatus internalization into alveolar epithelial cells with the increase of intracellular phosphatidic acid by activating FAK. Issue 1 (1st January 2021) - Han, Xuelin; Su, Xueting; Li, Zhiqian; Liu, Yanxi; Wang, Shuo; Zhu, Miao; Zhang, Changjian; Yang, Fan; Zhao, Jingya; Li, Xianping; Chen, Fangyan; Han, Li
ABSTRACT: Complement receptor 3 (CD11b/CD18) is an important receptor that mediates adhesion, phagocytosis and chemotaxis in various immunocytes. The conidia of the medically-important pathogenic fungus, Aspergillus fumigatus can be internalized into alveolar epithelial cells to disseminate its infection in immunocompromised host; however, the role of CR3 in this process is poorly understood. In the present study, we investigated the potential role of CR3 on A. fumigatus internalization into type II alveolar epithelial cells and its effect on host intracellular PA content induced by A. fumigatus . We found that CR3 is expressed in alveolar epithelial cells and that human serum and bronchoalveolar lavage fluid (BALF) could improve A. fumigatus conidial internalization into A549 type II alveolar epithelial cell line and mouse primary alveolar epithelial cells, which were significantly inhibited by the complement C3 quencher and CD11b-blocking antibody. Serum-opsonization of swollen conidia, but not resting conidia led to the increase of cellular phosphatidic acid (PA) in A549 cells during infection. Moreover, both conidial internalization and induced PA production were interfered by CD11b-blocking antibody and dependent on FAK activity, but not Syk in alveolar epithelial cells. Overall, our results revealed that CR3 is a critical modulator of Aspergillus fumigatus internalization into alveolar epithelial cells.